Management of Petanque Sports Development in Supporting Sports Achievements in East Java - Kurniawan, Genta; Sukmana, Abdian Asgi; Purnomo, Ardhi Mardiyanto Indra (CV. Nusantara Sporta, 2024)
The aim of this research is to determine the management of petanque sports development in supporting sports achievements in East Java. This type of research is descriptive qualitative. The population is coaches or administrators and FOPI athletes. The population used in this research were coaches or administrators and athletes, totalling 2-3 informants in each FOPI. Data collection uses observation, interview and documentation techniques. Next, the data was analyzed using descriptive data analysis techniques. The research results show that of the 3 FOPIs in East Java, there are several differences in organizational, training, facilities, infrastructure, and funding aspects. This research concludes that the management of petanque sports coaching carried out by FOPI Pasuruan City, Lamongan Regency and Kediri City has been going well, however for Pasuruan City, it needs to be improved from the coaching aspect because there is only 1 (one) active trainer. Achievement development has gone well because it has been proven that FOPI Lamongan Regency and Kediri City were able to come out as 1st (one) overall champion and 2nd (two) overall champion at the 2023 JATIM PORPROV event which was held in Mojokerto City.